2021
DOI: 10.3390/technologies9030048
|View full text |Cite
|
Sign up to set email alerts
|

Municipal Solid Waste Management Practices for Achieving Green Architecture Concepts in Addis Ababa, Ethiopia

Abstract: Solid waste is one of the social and environmental challenges that urban areas are facing. The study assesses the state of solid waste in Addis Ababa during 2016–2020 to provide implications for achieving green architecture concepts through better management of solid waste and its economic contribution. The study uses secondary and primary data. Quantitative and qualitative data are analyzed through descriptive statistics and context analysis, respectively. The result reveals that most solid waste is generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…In cities and towns of developing countries, solid waste management deficiencies were visible in many areas with little or no attention in those urban centers at all [ 8 ]. 30–50% of the generated urban center solid wastes of developing cities were thrown away on streets and open spaces causing serious health problems [ 9 ]. This is due to the lack of sufficient solid waste collection services [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In cities and towns of developing countries, solid waste management deficiencies were visible in many areas with little or no attention in those urban centers at all [ 8 ]. 30–50% of the generated urban center solid wastes of developing cities were thrown away on streets and open spaces causing serious health problems [ 9 ]. This is due to the lack of sufficient solid waste collection services [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a recent study in Addis Ababa showed that uncollected solid waste is disposed of the spaces, ditches, and rivers [9]. In Ethiopia, solid waste collection coverage is much higher in capital cities than in small towns, where a collection system is sometimes non-existent.…”
Section: Waste Collectionmentioning
confidence: 99%
“…These challenges may range from generating a large amount of waste to an inappropriate waste disposal system. According to a recent study conducted by Gelan [9] in Addis Ababa, the challenges include a lesser emphasis on MSWM by the government, the scarcity of land to perform different activities concerning solid waste management, particularly for temporary storage and disposal sites, financial scarcity, the lack of solid waste collection and transportation infrastructure, and the lack of skilled human resources. In addition, Teshome [12] stated that the MSWM systems in Ethiopia are irregular in collection and transportation, inadequate at waste prevention and collection coverage, inefficient from technical aspects, weak at the enforcement level of solid waste management policy and legal frameworks, and sometimes the presence of political interference in solid waste management.…”
Section: Challenges Of Municipal Solid Waste Management In Ethiopiamentioning
confidence: 99%
See 2 more Smart Citations